Auditory Brainstem and Middle Latency Responses Measured Pre- and Posttreatment for Hyperacusic Hearing-Impaired Persons Successfully Treated to Improve Sound Tolerance and to Expand the Dynamic Range for Loudness: Case Evidence - Formby, Craig; Korczak, Peggy; Sherlock, LaGuinn P.; Hawley, Monica L.; Gold, Susan (Seminars in Hearing, 2017)
In this report of three cases, we consider electrophysiologic measures from three hyperacusic hearing-impaired individuals who, prior to treatment to expand their dynamic ranges for loudness, were problematic hearing aid candidates because of their diminished sound tolerance and reduced dynamic ranges. Two of these individuals were treated with structured counseling combined with low-level broadband sound therapy from bilateral sound generators and the third case received structured counseling in combination with a short-acting placebo sound therapy. Each individual was highly responsive to his or her assigned treatment as revealed by expansion of the dynamic range by at least 20 dB at one or more frequencies posttreatment. Of specific interest in this report are their latency and amplitude measures taken from tone burst-evoked auditory brainstem response (ABR) and cortically derived middle latency response (MLR) recordings, measured as a function of increasing loudness at 500 and 2,000 Hz pre- and posttreatment. The resulting ABR and MLR latency and amplitude measures for each case are considered here in terms of pre- and posttreatment predictions. The respective pre- and posttreatment predictions anticipated larger pretreatment response amplitudes and shorter pretreatment response latencies relative to typical normal control values and smaller normative-like posttreatment response amplitudes and longer posttreatment response latencies relative to the corresponding pretreatment values for each individual. From these results and predictions, we conjecture about the neural origins of the hyperacusis conditions (i.e., brainstem versus cortical) and the neuronal sites responsive to treatment. The only consistent finding in support of the pre- and posttreatment predictions and, thus, the strongest index of hyperacusis and positive treatment-related effects was measured for MLR latency responses for wave Pa at 2,000 Hz. Other response indices, including ABR wave V latency and wave V-V′ amplitude and MLR wave Na-Pa amplitude for 500 and 2,000 Hz, appear either ambiguous across and/or within these individuals. Notwithstanding significant challenges for interpreting these findings, including associated confounding effects of their sensorineural hearing losses and differences in the presentation levels of the toneburst stimuli used to collect these measures for each individual, our limited analyses of three cases suggest measures of MLR wave Pa latency at 2,000 Hz (reflecting cortical contributions) may be a promising objective indicator of hyperacusis and dynamic range expansion treatment effects.
Keywords: Hyperacusis; toneburst ABR and MLR amplitude and latency measures; categorical loudness judgments; treatment to induce dynamic range expansion